SIMULATION ANALYSIS USING SIMPLE NETWORK LAN PACKET PRACER - Muhammad Azhar Putra Lambitu; Indrianto, SKom, MT Indrianto, SKom, MT (Jurnal Sistem Komputer, 2010)
This explains the scientific writing about the design of a simple LAN network using Packet Tracer simulator. In this scientific writing, use a simulator, ie Packet Tracer.5.0. Through this simulator we can create a simulation of a LAN, MAN and WAN. So if we want to create a network, we can take into account other what we need in making the network before getting directly into the field. So we can minimize mistakes and can further cut costs.